STUDI DESKRIPTIF PEMBELAJARAN BERNYANYI SISWA SMP N 29 PADANG - Ronal Yulmiando; Ardipal Ardipal; Jagar Lumban Toruan (SENDRATASIK UNP, 2014)
ABSTRACK   The aim of this research was to describe the learning process in singing class at SMPN 29 Padang by using demonstration method. This was qualitative research which used descriptive analysis method. The data was collected through observation, interview, documentation and library study. The data gotten then was classified, described and a conclusion was drawn. The result of the research indicated that the use of demonstration method did not help much in Improving the students' learning achievement maximally as : (1) the demonstration method was not applied maximally and so was the teacher' efforts, (2) the teacher's lack of skill in singing, (3) the learning media used was not as it should be, and (4) the students' musical experience was still low. Key words : Learning, Singing, Demonstration